1998
DOI: 10.1097/00005537-199806000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Supraselective Embolization in Intractable Epistaxis: Review of 45 Cases

Abstract: Epistaxis is a common and in most cases benign event. Severe or recurrent epistaxis, however, can present therapeutic problems. Forty-five cases of supraselective embolization in intractable epistaxis are reported. The authors' success rate of 97%, similar to the success rates reported in the literature, confirms the effectiveness of this technique. Complications occurred in only 8% of the cases. One serious complication was neurologic. Percutaneous embolization is an effective option for managing intractable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(52 citation statements)
references
References 8 publications
4
45
0
3
Order By: Relevance
“…Endovascular approaches are a viable alternative to surgical intervention for life-threatening nasal hemorrhage, with overall reported success rates of 71% to 100%. 1,20 Complications of endovascular embolization are usually minor, including sinusitis, septal perforation, otitis media, facial pain, headache, jaw pain, and facial edema or numbness. 2 Major complications, however, can occur.…”
mentioning
confidence: 99%
“…Endovascular approaches are a viable alternative to surgical intervention for life-threatening nasal hemorrhage, with overall reported success rates of 71% to 100%. 1,20 Complications of endovascular embolization are usually minor, including sinusitis, septal perforation, otitis media, facial pain, headache, jaw pain, and facial edema or numbness. 2 Major complications, however, can occur.…”
mentioning
confidence: 99%
“…However it is usually only mild and does not require medical attention, and only 6% of patients with epistaxis will require medical help (20). Various causes of epistaxis include dryness of the nasal cavity, digital trauma to the nasal cavity, hypertension, anticoagulation, and blood dyscrasias (7,12).…”
Section: █ Resultsmentioning
confidence: 99%
“…The cure rate achieved in most reported series is 80% or higher, particularly when the ipsilateral facial artery and contralateral sphenopalatine artery are simultaneously embolized. [7][8][9][10][11][12] Some have even used a mixture of hystoacril with Lipiodol (Guerbet, Paris, France). 13 The reported complication rates are very variable.…”
Section: Head and Neckmentioning
confidence: 99%
“…13 The reported complication rates are very variable. Minor complication rates range between 2.2 and 25%, [7][8][9]11,12,14 although Oguni et al have reported a rate of 45%, attributing this to the difference in definition of minor complication. 15 Serious complication rates vary between 0 and 6% when looking at large series.…”
Section: Head and Neckmentioning
confidence: 99%